Challenges in dealing with water pollution issues in the West Java island - Jamaludin Zainal Abidin (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Water is the most basic need for all living things on Earth. The abundance of water on Earth makes humans indifferent to the efficient use of water, including human activities, which are said to cause increasing pollutant loads in surface waters. The western part of Java, consisting of DKI Jakarta, West Java and Banten, has the highest population pressure in all parts of Indonesia. This has led to a decrease in the environment's carrying capacity, especially in the region's water resources. Agricultural and industrial activities and household activities cause decreasing water availability in quantity and reducing water quality. This has become a trigger for water scarcity both in quantity and quality. Based on the data, the western part of Java Island has rivers with critical status. In this study, researchers will analyze water availability, water pollution problems, and challenges in overcoming water pollution, especially in the western part of Java Island. This study used a qualitative method by conducting a literature review. In overcoming water pollution, serious efforts need to be made, including increasing community participation in the manufacture of household-scale WWTPs, limiting the use of pesticides in agricultural activities, and improving water quality by improving land cover in the upstream area and increasing water absorption in urban areas.